Behavior problems, social competence and academic performance: A comparative study of children in the school and family environments - Bolsoni-Silva, Alessandra [UNESP]; Perallis, Claudya [UNESP]; Nunes, Patricia [UNESP] (My University, 2018)
The simultaneous study of child behavior in both the family and school environment can be relevant for the prevention of behavior problems. The present paper aimed to describe and compare the prevalence of behavior problems, social competence and academic performance in children with problems only in the school environment, only in the family environment or in both. Teachers, mothers, fathers and caregivers of 77 children with behavior problems participated in the study (pre-school and schoolage children, boys and girls). The instruments used were: the CBCL Child Behavior Checklist and the TRF Teachers Report Form. The results showed a higher frequency of behavior problems and lower academic/social performance in children with problems in both environments, compared to those with problems only in the school or family environment. The teachers identified more internalizing problems when children showed problems only in the family environment and more internalizing/externalizing problems when this occurred in both environments. It was concluded that children who presented problems in both contexts had less social and academic competence.
Keywords: Academic competence; Behavior problems; Family; School; Social competence